Silicon nanowire based high brightness, pulsed relativistic electron source - Deep Sarkar; Prashant Kumar Singh; G. Cristoforetti; Amitava Adak; Gourab Chatterjee; Moniruzzaman Shaikh; Amit D. Lad; P. Londrillo; Giuseppe D’Arrigo; J. Jha; M. Krishnamurthy; L. A. Gizzi; et al. (APL Photonics, 2017)
We demonstrate that silicon nanowire arrays efficiently emit relativistic electron pulses under irradiation by a high-intensity, femtosecond, and near-infrared laser (∼1018 W/cm2, 25 fs, 800 nm). The nanowire array yields fluxes and charge per bunch that are 40 times higher than those emitted by an optically flat surface, in the energy range of 0.2–0.5 MeV. The flux and charge yields for the nanowires are observed to be directional in nature unlike that for planar silicon. Particle-in-cell simulations establish that such large emission is caused by the enhancement of the local electric fields around a nanowire, which consequently leads to an enhanced absorption of laser energy. We show that the high-intensity contrast (ratio of picosecond pedestal to femtosecond peak) of the laser pulse (10−9) is crucial to this large yield. We extend the notion of surface local-field enhancement, normally invoked in low-order nonlinear optical processes like second harmonic generation, optical limiting, etc., to ultrahigh laser intensities. These electron pulses, expectedly femtosecond in duration, have potential application in imaging, material modification, ultrafast dynamics, terahertz generation, and fast ion sources.